PENGARUH PROFITABILITAS, PERTUMBUHAN PENJUALAN, STRUKTUR AKTIVA DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Elsa Tria Harina (Universitas Negeri Padang, 2018)
The study aims to analyze: 1) the influence of profitability to capital structure , 2) the influence of growth of sales to capital structure 3) the influence of asset structure to capital structure and 4) the influence of firm size to capital structure. This research is causative research. The population in this research is property and real estate company registered in BEI in 2011 until 2016. Sample was determined by purposive sample method and 20 companies were selected as sample. The data used in this research is secondary data obtained from www.idx.co.id. Data collection techniques with documentation techniques. The analytical method useds multiple linear regression analysis with SPSS version 21 for windows. The result showed that the profitability has positive effect significant on capital structure, growth of sales has negative effect insignificant on capital structure, asset structure has negative effect insignificant on capital structure and firm size has positive effect significant on capital structure. Determination of capital structure is an important issue for every company because good and bad capital structure will have a direct effect on the company's financial position. Therefore companies should pay attention to selected funding decision. Keyword: Capital Structure, Profitability, Growth of Sales, Asset Structure, Firm Size